2019
DOI: 10.1016/j.cmet.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Cell Clustering Promotes a Metabolic Switch that Supports Metastatic Colonization

Abstract: Highlights d Loss of attachment causes mitochondrial perturbations and ROS production d Detached cancer cells cluster, inducing hypoxia, mitophagy, and reductive metabolism d This response clears damaged mitochondria and reduces mitochondrial ROS production d The clustering-induced metabolic switch promotes metastatic capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 46 publications
6
114
0
Order By: Relevance
“…We noted that the constraints on proliferation for those CTCs able to grow eventually are significantly reduced once single CTCs achieve a critical mass. This suggests that cell-cell contact mitigates stress, in line with recent findings on the survival advantage of CTC clusters 23,27 .This also indicates that compounds promoting CTC proliferation can be applied in the short term, and need not confound the downstream characterization of CTC biology. Our…”
Section: Discussionsupporting
confidence: 83%
“…We noted that the constraints on proliferation for those CTCs able to grow eventually are significantly reduced once single CTCs achieve a critical mass. This suggests that cell-cell contact mitigates stress, in line with recent findings on the survival advantage of CTC clusters 23,27 .This also indicates that compounds promoting CTC proliferation can be applied in the short term, and need not confound the downstream characterization of CTC biology. Our…”
Section: Discussionsupporting
confidence: 83%
“…Although the existence of CTC clusters has been known for decades [51][52][53][54][55], the biological mechanisms behind their formation, survival, dissemination, and superior metastatic ability are only partially understood [48]. Recently, an in vitro study has suggested that cell aggregation might protect the clustered cells from reactive oxygen species (ROS) that are produced in response to detachment from the extracellular matrix, by inducing hypoxiainducible factor 1-alpha (Hif1α)-mediated mitophagy of ROS-producing mitochondria [56]. The consequences of this response are a metabolic switch to glycolysis and an increment of survival and metastatic capacity.…”
Section: Single Ctcs Versus Ctc Clustersmentioning
confidence: 99%
“…It has been suggested that common hexoses other than glucose, such as galactose and fructose, are also involved in the growth and metastasis of cancer cells. Galactose has been shown to induce OXPHOS-dependent metabolism and suppress the growth and metastasis of cancer cells [ 84 , 85 , 86 ]. On the other hand, fructose has been shown to promote liver metastasis in colon cancer and breast cancer [ 87 ].…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…The antioxidant system is enhanced in circulating cancer cells in order to remove the increased amounts of ROS resulting from the activation of OXPHOS [ 99 ]. In addition, to prevent cell death due to the ROS, some cancer cells create a hypoxic environment by clustering, and induce mitophagy and glycolytic metabolism [ 84 ]. Thus, the metabolic reprogramming of cancer cells found in the blood circulation plays an important role in determining the metastatic target and the formation of metastatic foci [ 100 , 101 , 102 ].…”
Section: Tumor Metabolismmentioning
confidence: 99%